Taḥlīlu Ma’āniy Kalimati al Jihādi fī Aḥādiṡi Ṣaḥiḥi al Bukhāri - Yusuf, Muhammad; Nurlaily, Nurlaily (Al-Uslub: Journal of Arabic Linguistic and Literature, 2021)
The purpose of this study is to: find out the sentence jihad in the sahih bukhori hadith and parts of the jihad sentence in the sahih bukhori hadith, and to be able to find out what the meaning of the jihad sentence in the sahih bukhori hadith is. This type of research is qualitative in nature and the data sources used in this study are taken from library materials such as books, books, journals, and other types of library sources, which are related to hadiths about jihad. The data collection technique used is the Data Analysis Technique, the author uses a descriptive method, to analyze the research data, namely by: The researcher reads several hadiths on the theme of jihad, the researcher chooses sentences that contain jihad in the hadith about jihad, the researcher collects the hadiths that contain the sentence jihad, Researchers classify the types of jihad from the book of hadith Sahih Bukhari. The findings of this study are in accordance with the data that has been collected that the meaning of the sentence jihad in the sahih bukhori hadith is not only about war against infidels but in the book it also explains about fighting lust, fighting polytheists, and fighting wrongdoers. And so is the wisdom of each of these hadiths that they are different and need to be assisted with syarah from the Sahih bukhori hadith book so that there are no mistakes in the wisdom